2016
DOI: 10.1016/j.diabres.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiovascular and metabolic outcomes in people with type 2 diabetes on insulin versus non-insulin glucose-lowering therapies (GLTs): A systematic review and meta-analysis of clinical trials

Abstract: Objectives: To compare the cardiovascular and metabolic outcomes of Insulin versus noninsulin glucose lowering therapy (GLT).Methods: We included randomised control trials (RCTs) which randomised patients aged >18 years with Type 2 Diabetes (T2D) to insulin vs non-insulin GLT. We used risk ratios (RR), risk difference (RD) and odds ratios (OR) with 95% confidence interval (95%CI) to analyse the treatment effects of dichotomous outcomes and mean differences (with 95% CI) for continuous outcomes.Results: We incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Early insulin did not significantly alter a composite CV outcome of CV death, non-fatal MI and stroke, revascularization and hospitalization for heart failure compared with standard care (HR 1.04; 95% CI 0.97-1.11; P = 0.27).P = 0.71) and CV mortality (RR 0.99, 95% CI 0.90-1.09; P = 0.94) versus patients treated with other glucose-lowering medications, and similar rates versus those treated with diet or placebo (RR 0.92, 95% CI 0.80-1.07; P = 0.31, and RR 0.95, 95% CI 0.77-1.18; P = 0.64, respectively] 51. Consistent with these findings, another meta-analysis of 18 randomized trials in a total of 19 300 people with type 2 diabetes found no significant difference in the risk of all-cause mortality and CV events between groups treated with insulin compared with other glucose-lowering agents (RR 1.01, 95% CI 0.96-1.06; P = 0.69) 52. Extensive evidence from type 1 diabetes, especially with the Diabetes Control and Complications Trial (DCCT)/Epidemiology of Diabetes Interventions and Complications (EDIC) study, indicates that insulin therapy does not increase CV risk 53.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Early insulin did not significantly alter a composite CV outcome of CV death, non-fatal MI and stroke, revascularization and hospitalization for heart failure compared with standard care (HR 1.04; 95% CI 0.97-1.11; P = 0.27).P = 0.71) and CV mortality (RR 0.99, 95% CI 0.90-1.09; P = 0.94) versus patients treated with other glucose-lowering medications, and similar rates versus those treated with diet or placebo (RR 0.92, 95% CI 0.80-1.07; P = 0.31, and RR 0.95, 95% CI 0.77-1.18; P = 0.64, respectively] 51. Consistent with these findings, another meta-analysis of 18 randomized trials in a total of 19 300 people with type 2 diabetes found no significant difference in the risk of all-cause mortality and CV events between groups treated with insulin compared with other glucose-lowering agents (RR 1.01, 95% CI 0.96-1.06; P = 0.69) 52. Extensive evidence from type 1 diabetes, especially with the Diabetes Control and Complications Trial (DCCT)/Epidemiology of Diabetes Interventions and Complications (EDIC) study, indicates that insulin therapy does not increase CV risk 53.…”
mentioning
confidence: 70%
“…A meta‐analysis of 20 randomized trials involving 18 599 patients with type 2 diabetes found that those treated with insulin had similar rates of all‐cause mortality (relative risk [RR] 0.99; 95% CI 0.92‐1.06; P = 0.71) and CV mortality (RR 0.99, 95% CI 0.90‐1.09; P = 0.94) versus patients treated with other glucose‐lowering medications, and similar rates versus those treated with diet or placebo (RR 0.92, 95% CI 0.80‐1.07; P = 0.31, and RR 0.95, 95% CI 0.77‐1.18; P = 0.64, respectively] . Consistent with these findings, another meta‐analysis of 18 randomized trials in a total of 19 300 people with type 2 diabetes found no significant difference in the risk of all‐cause mortality and CV events between groups treated with insulin compared with other glucose‐lowering agents (RR 1.01, 95% CI 0.96‐1.06; P = 0.69) …”
Section: Antidiabetic Drugs and CV Effectsmentioning
confidence: 99%
“…Favourable cardiovascular outcomes of intensive glycaemic control using sulphonylureas or insulin versus conventional therapy using diet control were documented in the 10‐year follow‐up UK Prospective Diabetes Study; however, other RCTs either showed no significant benefits of insulin therapy on cardiovascular outcomes or revealed a link between insulin‐based therapy and a greater number of non‐fatal cardiovascular events . Recently, two meta‐analyses of RCTs suggested a neutral effect of insulin therapy on cardiovascular outcomes . These study findings should be interpreted with caution, however, because the studies included a limited number of cardiovascular events and shorter follow‐up periods, the sulphonylureas used might also have had detrimental effects on cardiovascular disease (CVD), and the study populations were specific to either patients at an early stage of diabetes or those with existing CVD .…”
Section: Introductionmentioning
confidence: 91%
“…13 Recently, two meta-analyses of RCTs suggested a neutral effect of insulin therapy on cardiovascular outcomes. 14,15 These study findings should be interpreted with caution, however, because the studies included a limited number of cardiovascular events and shorter follow-up periods, the sulphonylureas used 10,12 might also have had detrimental effects on cardiovascular disease (CVD), 16 and the study populations were specific to either patients at an early stage of diabetes 11 or those with existing CVD. 12,13 Conversely, longitudinal cohort studies have shown an association between insulin therapy and increased risk of CVD and all-cause mortality in patients with T2DM, but the effects of insulin therapy were only assessed in patients at an early stage of the antidiabetic treatment course, with insulin being used as monotherapy, or as second-line or third-line antidiabetic treatment.…”
Section: Introductionmentioning
confidence: 91%
“…The role of insulin should be considered carefully, turning out to be an important predictor of death. A meta-analysis of RCTs found no difference in the risk of all-cause mortality [RR= 1.00 (0.93 -1.08)] between Insulin and non-insulin glucose-lowering therapies in diabetes2 patients but at the same time it found an increased risk of hypoglycemia: RR= 1.90 (1.44 -2.51) [21]. In our observational approach the identification of the precise role of insulin as an independent predictor of death should have required other adjustments for clinical indicators of severity and for complications of diabetic disease and its treatment, but this was not the purpose of this research.…”
Section: Discussionmentioning
confidence: 99%